Про можливість зворотного формілування амінокислот в тканинах щурів у дослідах in vivo та in vitro - Гулий, М.Ф.; Сілонова, Н.В.; Печенова, Т.М.; Шевцова, Н.Ф. (Видавничий дім "Академперіодика" НАН України, 2007)
On the in vitro and in vivo systems of different rat tissues, the reversibility of the processes of enzymatic interaction between free amino acids and formate is demonstrated. Their dependence on the intracellular localization, duration of the interaction, and concentrations of formate and amino acids is studied.